2016
DOI: 10.1093/cercor/bhw360
|View full text |Cite
|
Sign up to set email alerts
|

The Basal Radial Glia Occurs in Marsupials and Underlies the Evolution of an Expanded Neocortex in Therian Mammals

Abstract: A hallmark of mammalian brain evolution is the emergence of the neocortex, which has expanded in all mammalian infraclasses (Eutheria, Marsupialia, Monotremata). In eutherians, neocortical neurons derive from distinct neural stem and progenitor cells (NPCs). However, precise data on the presence and abundance of the NPCs, especially of basal radial glia (bRG), in the neocortex of marsupials are lacking. This study characterized and quantified the NPCs in the developing neocortex of a marsupial, the tammar wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…To determine the main period of neurogenesis, specifically the timing of deep and upper layer generation, in the domestic cat, pig and sheep neocortex, we analysed cortical sections from a broad range of developmental stages by immunohistochemistry for specific neuronal markers, that is Tbr1 characteristically expressed by deep layer neurons and Brn2 characteristically expressed by upper layer neurons (He et al., ; McEvilly et al., ; Hevner, ; Molyneaux et al., ; Toma and Hanashima, ; Sauerland et al., ). In all three species analysed, Tbr1+ neurons were born at early stages during development and predominantly accumulated in the deep layers of the CP whereas Brn2+ neurons were born at later stages during development and predominantly accumulated in the upper layers of the CP (Figs 1–3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine the main period of neurogenesis, specifically the timing of deep and upper layer generation, in the domestic cat, pig and sheep neocortex, we analysed cortical sections from a broad range of developmental stages by immunohistochemistry for specific neuronal markers, that is Tbr1 characteristically expressed by deep layer neurons and Brn2 characteristically expressed by upper layer neurons (He et al., ; McEvilly et al., ; Hevner, ; Molyneaux et al., ; Toma and Hanashima, ; Sauerland et al., ). In all three species analysed, Tbr1+ neurons were born at early stages during development and predominantly accumulated in the deep layers of the CP whereas Brn2+ neurons were born at later stages during development and predominantly accumulated in the upper layers of the CP (Figs 1–3).…”
Section: Resultsmentioning
confidence: 99%
“…This is the first study that defines the main period of neurogenesis, specifically the timing of deep and upper layer generation, in the developing domestic cat, pig and sheep neocortex using immunohistochemical markers for distinct neuronal subtypes, that is Tbr1 and Brn2. We found that the general sequence of neural events is preserved among cat, pig, sheep and other mammalian species as deep and upper layer neurons are produced in an ‘inside ‐ out’ manner with Tbr1+ deep layer neurons being generated early and Brn2+ upper layers being generated at later stages during development (Kriegstein et al., ; Hevner, ; Molyneaux et al., ; Toma and Hanashima, ; Sauerland et al., ; Darnell and Gilbert, ). However, we observed differences in the timing of the cortical neurogenic period when cat, pig and sheep were compared with the sheep exhibiting the longest neurogenic period and the pig showing a longer neurogenic period when compared to the cat.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Postmitotic neurons downregulate TBR2 and instead express TBR1, and/or other transcription factors that specifically define their projection fate (Götz et al 1998, Hevner et al 2001, Englund et al 2005, Sessa et al 2008, as further described in detail in section 1.5 below. Comparable mRNA and protein expression patterns of important developing transcription factors specifying radial glial cells (PAX6), intermediate progenitor cells (TBR2) and postmitotic neurons (TBR1, TLE4, CUX1, CUX2, NEUROD6) have been described in marsupials as well, suggesting that some aspects of the transcriptional regulation of neuronal differentiation might be conserved across therian mammals (Cheung et al 2010, Sauerland et al 2016. The majority of the transcription factors so far identified in marsupials belong to a general and early molecular network of neuronal differentiation, while the molecular specification of later stages of cortical development are yet to be fully elucidated in non-eutherian mammalian species.…”
Section: Radial Glia and Intermediate Progenitorsmentioning
confidence: 99%